Mansonella ozzardi in Amazonas, Brazil: prevalence and distribution in the municipality of Coari, in the middle Solimões River - Marilaine Martins; Felipe Arley Costa Pessoa; Maurício Borborema de Medeiros; Edmar Vaz de Andrade; Jansen Fernandes Medeiros (Memorias do Instituto Oswaldo Cruz, 2010)
This study investigated some epidemiological aspects of the Mansonella ozzardi in municipality of Coari, Amazonas. Clinical symptoms were correlated with the filarial infection and the parasitic infection rates (PIR) were estimated in simuliid vectors. The general M. ozzardi human prevalence rate was 13.3% (231/1733), of which 10.2% (109/1069) were from the urban area and 18.4% (122/664) from the rural area. The prevalence rates were higher in men (14.5% urban and 19.7% rural) than in women (6.7% urban and 17.2% rural) and occurred in most age groups. The indices of microfilaremics were higher in people > 51 years old (26.9% urban and 61.5% rural). High prevalence rates were observed in retired people (27.1% urban area), housewives and farmer (41.6% and 25%, respectively, in rural area). The main clinical symptoms were joint pains and sensation of leg coldness. Only Cerqueirellum argentiscutum (Simuliidae) transmits M. ozzardi in this municipality (PIR = 5.6% urban and 7.1% rural). M. ozzardi is a widely distributed parasitic disease in Coari. Thus, temporary residency in the region of people from other localities involved with the local gas exploitation might be a contributing factor in spreading the disease.